2021
DOI: 10.1037/edu0000627
|View full text |Cite
|
Sign up to set email alerts
|

A learning method for all: The testing effect is independent of cognitive ability.

Abstract: The testing effect, defined as the positive effect of retrieval practice (i.e., self-testing) on long-term memory retention relative to other ways to support learning, is a robust empirical phenomenon. Despite substantial scientific evidence for the testing effect, less is known about its effectiveness in relation to individual differences in cognitive ability. In the present study, we examine whether the effect of retrieval practice is beneficial independent of cognitive ability using behavioral and brain ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 66 publications
4
46
0
Order By: Relevance
“…The performance difference between retrieval practice and other ways of attaining information-most commonly re-reading-is denoted as the "testing effect." The testing effect is supported by both behavioral and functional fMRI evidence (for overviews, see Dunlosky et al, 2013;van den Broek et al, 2016;Adesope et al, 2017;Antony et al, 2017;Moreira et al, 2019;Jonsson et al, 2020). Research that currently underway shows that measures of brain activity following the testing effect (retrieval practice > study) and the "CMR effect" (CMR > AR) indicate that the same brain areas are activated.…”
Section: Implications and Future Researchmentioning
confidence: 95%
“…The performance difference between retrieval practice and other ways of attaining information-most commonly re-reading-is denoted as the "testing effect." The testing effect is supported by both behavioral and functional fMRI evidence (for overviews, see Dunlosky et al, 2013;van den Broek et al, 2016;Adesope et al, 2017;Antony et al, 2017;Moreira et al, 2019;Jonsson et al, 2020). Research that currently underway shows that measures of brain activity following the testing effect (retrieval practice > study) and the "CMR effect" (CMR > AR) indicate that the same brain areas are activated.…”
Section: Implications and Future Researchmentioning
confidence: 95%
“…Importantly, evidence suggests that at least some of the learning strategies identified above (see Knowledge in the course description) are beneficial irrespective of cognitive ability. For instance, retrieval practice shows benefits for low-, medium-, and high-cognitive ability students (as assessed by a comprehensive composite of fluid intelligence, working memory, short-term memory, and episodic memory scores, among others; Jonsson et al, 2020; see also Bertilsson et al, 2020), and mnemonics provides comparable benefits for students with low-, medium-, and highlearning ability levels (for vocabulary learning; Pressley et al, 1980). Armed with effective learning strategies and the commitment to use them, students who face inequities in instructional, environmental, or personal contexts-or those at lower cognitive ability levelscould plausibly show significant gains in achievement (e.g., see Fink et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The current study is part of a large data collection aimed at answering questions related to cognitive learning strategies (see also Jonsson et al, 2020a;Jonsson, Wiklund-Hörnqvist, Stenlund, Andersson, & Nyberg, 2020b;Wiklund-Hornqvist, Stillesjö, Andersson, Jonsson, & Nyberg, 2021). At the outset, 324 pupils were recruited for the data collection from third year classes in local upper secondary schools.…”
Section: Participantsmentioning
confidence: 99%
“…Importantly, each remaining participant in the current fMRI study (N = 70) was categorized as low (n = 17), intermediate (n = 21) or high (n = 32) relative to the larger sample, making the categorization of participants in the current study less biased and more robust. In addition, a rationale for categorizing the participants in the current study into the three groups was to be able to relate to the study by Jonsson et al (2020b) also theoretically. Jonsson and colleagues observed that the magnitude of the testing effect (the effect of another active learning method which compares vocabulary learning using retrieval practice with study) was independent of cognitive ability (low/intermediate/high), and we wanted to be able to investigate whether similar conclusions would follow when comparing CMR to AR (i.e.…”
Section: Cognitive Ability Measuresmentioning
confidence: 99%
See 1 more Smart Citation